Being a mother and a nurse: issues about gender and overlapping social roles - Bruna Caroline Rodrigues; Muriel Fernanda de Lima; Bruno Maschio Neto; Graziela Lopes de Oliveira; Aurea Christina de Paula Corrêa; Ieda Harumi Higarashi (Universidade Federal do Ceará, 2017)
to describe the experiences of nursing mothers in the reconciliation of their social roles. Methods: this is a qualitative study with 10 nursing mothers. Participants were selected using the snowball method, and through semi-structured interviews. The data were analyzed by the content analysis. Results: the data found led to the configuration of three categories: Learning to be a mother, Reconciling the different social roles: being a mother, wife and professional, and The father as an active participant in raising children. Conclusion: although maternity is considered an important milestone in the life of the subjects, they highlighted the resumption of professional life as a condition for the achievement of self-esteem and better social interaction, even with the emergence of difficulties such as return to work, absence in their families and the configuration of a support network.